2007
DOI: 10.1016/j.jat.2006.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Shannon entropy of symmetric Pollaczek polynomials

Abstract: We discuss the asymptotic behavior (as n → ∞) of the entropic integrals E n = −

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…where c is a positive constant; see [21,[393][394][395][396][397][398][399][400] for a detailed description. We should like to mention, as a brief guide to the reader, some recent literature on the Pollaczek polynomials; see [22] for the asymptotic behavior of the polynomials for x / ∈ [−1, 1]; [2,24] for the asymptotic behavior of their zeros and [14,15,23] for applications to physical problems. Regarding weighted polynomial approximation in L p with respect to a class of exponential weights on [−1, 1] that violate the Szegö conditions, see [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…where c is a positive constant; see [21,[393][394][395][396][397][398][399][400] for a detailed description. We should like to mention, as a brief guide to the reader, some recent literature on the Pollaczek polynomials; see [22] for the asymptotic behavior of the polynomials for x / ∈ [−1, 1]; [2,24] for the asymptotic behavior of their zeros and [14,15,23] for applications to physical problems. Regarding weighted polynomial approximation in L p with respect to a class of exponential weights on [−1, 1] that violate the Szegö conditions, see [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…; see e.g. [3,4,7,10,11,12,13,20] and the references therein. In particular, it has been shown that for Chebyshev orthonormal polynomials of the first kind the relative entropy K n does not depend on n,…”
Section: Introductionmentioning
confidence: 99%